Tingkat Integrasi Pengetahuan Lingkungan dalam Pembelajaran Kimia Oleh Guru Kimia di Kabupaten Aceh Besar - Lusiana Dongoran; Adean Mayasri (PendIPA Journal of Science Education, 2026)
This study aimed to determine the level of environmental knowledge integration in chemistry learning conducted by chemistry teachers in Aceh Besar Regency. The study employed a qualitative descriptive approach involving five chemistry teachers from five senior high Schools in Aceh Besar Regency who had completed the Teacher Professional Education Program (PPG) and were selected through purposive sampling. Data were collected through questionnaires, document analysis, and structured interviews. The data were analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the integration of environmental knowledge in chemistry learning was categorized as good to very good. The learning implementation aspect obtained the highest percentage (91%) and was classified as very good, followed by teacher attitude (89%), learning planning (86,67%), and learning resources and media (82,67%). Meanwhile, the assessment aspect obtained the lowest percentage (78,67%) and was categorized as good. Document analysis indicated that environmental issues had been integrated into learning objectives, materials, learning activities, learning resources and media, as well as assessment instruments. Interview results further demonstrated that teachers possessed positive awareness the importance of integrating environmental knowledge into chemistry learning. However, the integration tended to remain contextual and had not yet fully developed into learning activities that emphasize in-depth environmental problem-solving.